The old question: which programming language should we choose to teach to program? - Sobral, Sónia Rolland (2021)
When students enter higher education in computer courses, students have, in the first semester, to perceive and streamline computer (or computational) thinking the names for the unit are diverse, usually algorithm and programming, introduction to programming or even Programming I or algorithm. [...]